2005
DOI: 10.1038/sj.bjp.0706390
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine‐induced endothelium‐dependent contractions in the SHR aorta: the Janus face of prostacyclin

Abstract: 1 In the spontaneously hypertensive rat (SHR) and aging Wistar-Kyoto rats (WKY), acetylcholine releases an endothelium-derived contracting factor (EDCF) produced by endothelial cyclooxygenase-1, which stimulates thromboxane A 2 receptors (TP receptors) on vascular smooth muscle. The purpose of the present study was to identify this EDCF by measuring changes in isometric tension and the release of various prostaglandins by acetylcholine. 2 In isolated aortic rings of SHR, U 46619, prostaglandin (PG) H 2 , PGF 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

38
353
7
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(404 citation statements)
references
References 45 publications
38
353
7
6
Order By: Relevance
“…Endothelium-and cyclooxygenase-dependent contractions are prominent in the aorta of the spontaneously hypertensive rat (Lüscher and Vanhoutte, 1986;Yang et al, 2004a, b;Tang et al, 2007), the abdominal aorta of the diabetic rabbit and the femoral artery of the diabetic rat (Shi et al, 2007). The endothelium-derived contracting factor can be prostacyclin, thromboxane A 2 , endoperoxides, prostaglandin E 2 , hydroxyl radicals or superoxide anions depending on the animal model, the preparation and the agonist used Auch-Schwelk et al, 1990;Yang et al, 2004a, b;Gluais et al, 2005Gluais et al, , 2006Shi et al, 2007). Oxygen-derived free radicals facilitate endothelium-dependent contractions, and antioxidants effectively decreased them in the aorta of spontaneously hypertensive rats Yang et al, 2002Yang et al, , 2003bTang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelium-and cyclooxygenase-dependent contractions are prominent in the aorta of the spontaneously hypertensive rat (Lüscher and Vanhoutte, 1986;Yang et al, 2004a, b;Tang et al, 2007), the abdominal aorta of the diabetic rabbit and the femoral artery of the diabetic rat (Shi et al, 2007). The endothelium-derived contracting factor can be prostacyclin, thromboxane A 2 , endoperoxides, prostaglandin E 2 , hydroxyl radicals or superoxide anions depending on the animal model, the preparation and the agonist used Auch-Schwelk et al, 1990;Yang et al, 2004a, b;Gluais et al, 2005Gluais et al, , 2006Shi et al, 2007). Oxygen-derived free radicals facilitate endothelium-dependent contractions, and antioxidants effectively decreased them in the aorta of spontaneously hypertensive rats Yang et al, 2002Yang et al, , 2003bTang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…EDCF is unlikely to be a single substance but rather is constituted of a mixture of prostanoids, the formation of which depends on the vascular bed, the age, and the condition of the species studied. Thus prostacyclin (9,10,27), endoperoxides (7,14), and thromboxane A 2 (10,11,29) have been proposed as EDCFs. Cyclooxygenase breaks down arachidonic acid to form endoperoxides, which are subsequently converted into prostacyclin, thromboxane A 2 , prostaglandin D, prostaglandin E, and/or prostaglandin F by their respective synthases (3,20).…”
mentioning
confidence: 99%
“…[3][4][5] In spontaneously hypertensive rats (SHR) a well-described manifestation of endothelial dysfunction is an increased production of endotheliumderived contractile factors (EDCF). 6 Drug-intervention studies have shown that some anti-hypertensive treatments, for instance with angiotensin AT 1 receptor antagonists, not only lower blood pressure but also cause an improvement of endothelial function and regression of structural changes in resistance arteries. 7,8 Other anti-hypertensive treatments, for example, the selective β 1 -adrenoceptor antagonist atenolol, succeed in lowering blood pressure but did not reverse the structural changes or the endothelial dysfunction associated with hypertension.…”
Section: Introductionmentioning
confidence: 99%